To Preannounce or Not: New Product Development in a Competitive Duopoly Market - Klastorin, Ted; Mamani, Hamed; Zhou, Yong‐Pin (Production and Operations Management, 2016)
In this study, we consider the issue of preannouncing or not preannouncing the development of a new product. Our research is motivated by contrasting views in the literature and varying actions observed in practice. We develop and analyze a game theoretic model that examines the effect of a firm's preannouncement of its product development. Our model is based on a durable goods duopoly market with profit‐maximizing firms. The first firm is an innovator who initially begins developing the product; the second firm is an imitator that begins developing a competing product as soon as it becomes aware of the innovator's product. We assume that consumers are rationally expectant and purchase at most one unit of the product when they have maximum positive utility surplus that is determined by the characteristics of the product, the consumer's marginal utility, and the consumer's discounted utility for future expected products. The innovator firm can release information about its product when it begins developing the product or can guard information about its product until it introduces the product into the market. Our analysis and numerical tests show that, under some conditions, the innovator firm can benefit by preannouncing its product and giving the imitator firm additional time to differentiate its product. We discuss these conditions and their implications for new product development efforts.